Development of E-Modules Based on Local Potential in Grenden Village to Improve the Digital Literacy of Junior High School Students - Predina, Sherin Shintya; Wahyuni, Sri; Nuha, Ulin; Hasyim, Taufiqrahman (Journal of Innovative Science Education, 2025)
This study develop an e-module for Natural Science learning by integrating the local potential of Grenden Village to enhance junior high school students' digital literacy. The integration of local potential is relevant because it provides contextual learning experiences, making science concepts more relatable and engaging for students. The e-module was developed using the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. The research was conducted at SMP Negeri 2 Puger, involving 36 students. Key results indicate that the e-module achieved a validity score of 90% (highly valid), a practicality score of 94% (very practical), and an N-gain score of 0.64 (medium effectiveness). Additionally, student satisfaction reached 88%, reflecting a positive response. In conclusion, the e-module based on Grenden Village’s local potential is valid, practical, and effective in improving students' digital literacy. By integrating local contexts, it provides a meaningful learning experience, enhances student motivation, and supports independent learning.